2008
DOI: 10.1097/qad.0b013e3283112ba6
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy among a conflict-affected population in Northeastern Uganda: a qualitative study

Abstract: We aimed to determine patient and health worker concerns regarding antiretroviral adherence in a conflict-affected population using focus groups (n = 40) and semi-structured interviews (n = 11). Patient concerns include security attending clinics, food security, distance to health centers and access to health providers. During periods of famine and flooding, the lack of food security and only single daily meals makes taking multiple doses impossible. Possible facilitating strategies included mobile teams, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 3 publications
2
26
0
Order By: Relevance
“…Among low-income adults, food insecurity and other competing subsistence needs (eg, unstable housing) are associated with worsened access and adherence to care (151)(152)(153)(154) because competing subsistence priorities such as obtaining food and shelter often interfere with adherence to regular medication use or attendance at outpatient appointments (15,(155)(156)(157)(158)(159)(160)(161)(162)(163). Research on adherence to other long-term medication regimens, such as tuberculosis, has also indicated the importance of food security to adherence and treatment outcomes (164,165).…”
Section: Behavioral Pathwaysmentioning
confidence: 99%
“…Among low-income adults, food insecurity and other competing subsistence needs (eg, unstable housing) are associated with worsened access and adherence to care (151)(152)(153)(154) because competing subsistence priorities such as obtaining food and shelter often interfere with adherence to regular medication use or attendance at outpatient appointments (15,(155)(156)(157)(158)(159)(160)(161)(162)(163). Research on adherence to other long-term medication regimens, such as tuberculosis, has also indicated the importance of food security to adherence and treatment outcomes (164,165).…”
Section: Behavioral Pathwaysmentioning
confidence: 99%
“…In contrast, thoughts about drug toxicities, disruption of the daily routine, and acceptance of their HIV illness were of concern to only a minority of participants [13]. In a conflict-affected population in northeastern Uganda, individuals consuming only one meal a day and those dependant on caregivers for food were particularly prone to missing ART doses [52]. In Zambia, the belief that antiretrovirals must be taken with food has led individuals to skip doses in the absence of available or accessible food [53].…”
Section: Impact Of Food Insecurity On Hiv Treatment and Clinical Outcmentioning
confidence: 99%
“…This association has fostered a great deal of interest because of the links between poor adherence and HIV suppression, immunological decline and the progression of HIV to AIDS . A growing number of studies have demonstrated or at least called attention to the important links between food insecurity and ART initiation, adherence, and consistency of ARV consumption (see, e.g., Au et al, 2006;Nachega et al, 2006;Hardon et al, 2007;Olupot-Olupot et al, 2008;Sanjobo et al, 2008;Kalofonos, 2010). In each of these studies, food concerns took on different dimensions.…”
Section: Food Insecurity and Hiv/aidsmentioning
confidence: 99%